KAJI EKSPERIMENTAL PENGARUH PUTARAN PENGADUKAN TERHADAP KUALITAS BIODIESEL YANG DIHASILKAN DARI MINYAK JELANTAH - drajat indah mawarni (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2021)
Biodiesel is diesel engine fuel in the form of triglyceride compounds derived from biological resources in the form of vegetable fat oils and animal fats. Making this biodiesel using used cooking oil from food frying with KOH base catalyst and variations of stirring rotation 200, 300, 400 rpm. The transesterification reaction was initiated by heating used cooking oil with methanol and KOH catalyst at a temperature of 55C and various stirring cycles were carried out. The test was carried out at the Laboratory of Heat and Mass Transfer, Gajah Mada University, Yogyakarta. The purpose of this research is to make diesel engine fuel, to get the best stirring cycle used in the manufacture of biodiesel and to determine the quality of biodiesel, including Density Value, Viscosity, Calorific Value, Pour Point, Flash Point, Fog Point. Based on the tests carried out, it can be concluded that the best stirring rotation at 400 rpm is getting a Density Value of 891.9 kg/m3, a viscosity value of 5.2 cSt, and a 200 rpm getting the best Calorific Value 15.505 Btu/lb, a Pour Point Value of 12.33oC, a Cloud Point Value of 5.5 C and Flash Point Value 168.6oC